'The current mental health status of children and young people with JIA, and their wider family': a charity partner collaboration survey - Polly Livermore; S. Ainsworth; R. Beesley; S. Douglas; E. Earle; D. Wilson; L. Woolley; J. Clinch (BMC, 2023)
Abstract Background This paper presents insight into the scale of mental health concerns for families who have a child or young person with a diagnosis of Juvenile Idiopathic Arthritis (JIA) living in any of the four nations of the United Kingdom (UK). The study's objective is to share the current experiences of those that responded to a charity survey and consider future work to improve mental health support. Methods This work was initiated and led by five UK charity partner organisations working with families affected by JIA. Parents/carers of a child or young person with JIA, and young people with JIA, submitted self-completion online questionnaires. The questionnaire asked 19 core questions, with a focus on the mental health impact of having and living with a JIA diagnosis. Questionnaires were delivered via charity partner UK-wide mailing lists and social media. Results Questionnaire were completed by 291 participants over a 3-week period in February 2022. The majority of respondents were parents (229, 79%), 103 children had been diagnosed for over six years (35%), and 131 (45%) received shared care between paediatric rheumatology centres. In total, 168 (59%) children and young people with JIA had received, were currently receiving or were waiting for mental health support. Parents reported that their child's diagnosis impacted their own mental health (218, 82%). Children and young people reported never being offered mental health support during appointments for JIA (157, 54%), and 71 (50%) of these had never received support. Conclusion Children and young people with JIA have significant mental health sequelae from their diagnosis. Our findings found that nearly 60% of our respondents have had or are requiring mental health support, with significant numbers of parents/carers reporting difficulties in accessing care for their child's mental health or their own mental health, due to their child's diagnosis. This unique collaborative charity-led study, illustrates the importance of timely and accessible mental health support. Further work is needed to understand why best practice guidance for mental health support is not being met consistently and to identify how to embed it into standard rheumatology care.